Development of Student Worksheet on Materials Economy Based Problem Solving - Dewi Pratita; Ikbal Barlian; Rusmin Rusmin (Bina Nusantara University, 2018)
This research aimed to determine the validity, practicalities, and effectiveness development of student worksheet on materials economy based on problem solving for Junior High School students Yayasan Pendidikan Islam (YPI) Tunas Bangsa Palembang. This research was developed consisting of four stages; define, design, develop, and disseminate known as 4D development models. The instruments were the validation sheet, questionnaire, observation sheet, and test sheet. The research and development data consisted of the qualitativeand quantitative data. The qualitative data in the form of learning support facility, readability from the draft of student worksheet with problem-based instructions that were developed, and students’ response against using student worksheet with problem-based instructions. While the quantitative data was in the form of test results of student learning. Based on the results of this research, it concludes that the student developed worksheet with problem-based instruction is valid, practical, and effective, so it is very well used by the teacher as a supplement in teaching to complement the teaching materials in the learning process.